Gold nanoparticles enhanced dna biosensor based on silica interdigiated electrodes for detection of human papilloma virus / \c Nor Azizah Parmin. - Nor Azizah Parmin (Institute of Nano Electronic Engineering, Universiti Malaysia Perlis, 2018)
The intention of this research is to develop a portable, sensitive, selective, rapid, and label-free DNA detection on Nano chip-based Interdigitated Electrodes (IDE) for early detection of Human Papillomavirus (HPV) that cause cervical cancer by quantitative measurements. In this research study, IDE acts as a transducer for a low bio-cytotoxicity, and a low-concentration of HPV DNA using in vitro clinical samples. This project was accomplished with the following specific objectives ; to design the specific DNA sequences related to HPV genes on the modified IDE ; to develop and characterize the integrated GNPs with IDE based biosensor that acts as a transducer to convert qualitative bio reaction signal to quantitative electrical measurement ; to examine and validate the performance of the functionalized GNPs based IDE device for DNA of HPV detection based on electrical measurement of DNA hybridization using high-performance analysis.